Sex-related differences in the impact of nutritional status on length of hospital stay in atrial fibrillation: a retrospective cohort study - Kwaśny, Adrian; Łokieć, Katarzyna; Uchmanowicz, Bartosz; Młynarska, Agnieszka; Smereka, Jacek; Czapla, Michał (Frontiers in Public Health, 2023)
Background Nutritional status is related to the length of hospitalization of patients with atrial fibrillation (AF). The aim of this study is to assess the prognostic impact of nutritional status and body mass index on length of hospital stay (LOHS) among patients with AF relative to their sex. Methods A retrospective analysis of the medical records of 1,342 patients admitted urgently with a diagnosis of AF (ICD10: I48) to the Cardiology Department (University Hospital in Wroclaw, Poland) between January 2017 and June 2021. Results In the study group, women were significantly older than men (72.94 ± 9.56 vs. 65.11 ± 12.68, p < 0.001). In an unadjusted linear regression model, malnutrition risk was a significant independent predictor of prolonged hospitalization in men (B = 1.95, p = 0.003) but not in women. In the age-adjusted linear regression model, malnutrition risk was a significant independent predictor of prolonged hospitalization in men (B = 1.843, p = 0.005) but not in women. In the model adjusted for age and comorbidities, malnutrition risk was a significant independent predictor of prolonged hospitalization in men only (B = 1.285, p = 0.043). In none of the models was BMI score a predictor of LOHS in either sex. Conclusion The risk of malnutrition directly predicts the length of hospital stays in men but not women. The study did not find a relationship between body mass index and length of hospital stay in both women and men.